2016
DOI: 10.1007/s11255-016-1347-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complication rates related to male urethral slings and artificial urinary sphincters for urinary incontinence: national multi-institutional analysis of ACS-NSQIP database

Abstract: 3.0 %, p < 0.001). Patients with higher BMI were more likely to have a complication, while age, race and Charlson comorbidity index were not associated with higher or lower complication rates. Conclusions Complications rates for both male sling and AUS are low. Male sling is associated with a lower rate of complications than AUS. These findings allow for better patient perioperative counseling regarding 30-day perioperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…[3][4][5][6][7][8] Though overall success rates and satisfaction are high, the AUS is a procedure with many known potential complications. 5,9 Among the most severe of these complications are device infection and erosion, necessitating removal of the device in its entirety. 10 Known risk factors for device removal include diabetes, history of radiation or urethral stricture, 11 and higher American Society of Anesthesiologists (ASA) class.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Though overall success rates and satisfaction are high, the AUS is a procedure with many known potential complications. 5,9 Among the most severe of these complications are device infection and erosion, necessitating removal of the device in its entirety. 10 Known risk factors for device removal include diabetes, history of radiation or urethral stricture, 11 and higher American Society of Anesthesiologists (ASA) class.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the few studies to examine whether obesity had an impact on 30-day complications following male sling, Alwaal et al reported that men with a BMI of 40 or higher had a 12% incidence of 30-day complications compared with less than 4% of patients with a BMI of less than 40. 8 While there are overall low numbers in this study, it certainly lends credence to the subjective concerns of urologists performing surgery on morbidly obese patients. In addition, Sacco et al reported that patients with a BMI of 30 or higher and those with prior radiation experienced a higher incidence of failure within 6 months of surgery.…”
Section: Discussionmentioning
confidence: 64%
“…The MS is an attractive alternative for patients who wish to avoid mechanical handling during urinary voiding and intermediate data supports good safety and efficacy rate in men with mild to moderate degree of SUI. Furthermore, published literature supports that MS has lower complications rates than AUS (74). Nonetheless, the AMS 800 device remains the standard of treatment for complete continence and has the longest efficacy and safety records.…”
Section: Discussionmentioning
confidence: 96%